Bacterial contamination of saline used for epidural procedures in an obstetric setting: a randomised comparison of two drawing-up techniques. (February 2017) - Onofrei, M.; Wee, M.Y.; Parker, B.; Wee, N.; Hill, S.
Highlights: Epidural abscess in the obstetric population is rare but has severe consequences. Failure of aseptic technique is a risk factor for epidural abscess. There are two techniques of drawing up saline for the epidural procedure. Bacterial contamination occurred with both techniques. We recommend using individually wrapped sterile saline ampoules. Abstract: Background: There is little evidence to inform practice regarding the optimum aseptic technique of drawing up saline for epidural insertion. Our regional practice is to draw up saline from a non-sterile packaged plastic ampoule, therefore introducing the risk of bacterial contamination. Usually, the anaesthetist draws up saline directly from the vial held by an assistant using a needle (needle technique). Alternatively, the saline vial is emptied onto a sterile tray by an assistant and then drawn up by the anaesthetist (tray technique). We hypothesised that the latter will lead to an increase in the number of contaminated saline samples as they are exposed to the environment. Methods: In labour rooms and before epidural catheter insertion, 110 samples of saline 20 mL were randomly drawn up using our hospital's recommended epidural aseptic precautions, using either the needle or the tray technique. Equal amounts of saline were inoculated into aerobic and anaerobic blood culture bottles. Results: Eleven percent of samples in the needle arm and 24% of samples in the tray arm grew commensal micro-organisms including coagulase-negative Staphylococcus, Micrococcus luteus and Streptococcus viridans. A two-sided Fisher's exact test for categorical unpaired data showed no statistical difference between the two arms of the trial ( P =0.13). Conclusion: The difference in the saline contamination rate between the two techniques did not reach statistical significance. As bacterial contamination occurred with both techniques, we recommend using sterile saline pre-packaged in the epidural tray or individually wrapped sterile glass saline ampoules.